Female Leadership: Understanding Female Roles in Business, Gender-based Barriers to Senior Management Positions, and How to Make the Breakthrough - LU, Wenjun (2014)
Gender has become a significant issue in management and organization, which is worth to be noticed in both theory and practical perspectives. Also as the improvement of female education level, more successful female leaders/managers play important roles in business world. However, there still exist some traditional barriers for many women to develop their career. Therefore, understanding the patterns to make female leaderships distinctive is a modern topic, and researching the women different career path will contribute to further studies in leadership theories, gender theories and career theories.